A RANKING SYSTEM FOR HANDLING COVID-19 IN SOUTHEAST ASIAN USING AHP-COPRAS - Setyawan Wibisono; Wiwien Hadikurniawati; Arief Jananto; Taufiq Dwi Cahyono (STMIK Royal, 2022)
Abstract: One of the institutions that stated the poor handling of Covid-19 in Indonesia was the Lowy Institute. On March 13, 2021, Lowy Institute put Indonesia in 89th rank out of 102 countries that were successfully surveyed regarding the handling of the Covid-19 pandemic. This research is an attempt to critique the Lowy Institute's assessment. The COPRAS-AHP hybrid method was used. The AHP method, especially in the pairwise comparison section, is used as a method to determine the validity of the criterion weights. Five criteria were used in determining the ranking of the handling of the Covid-19 pandemic in countries in the Southeast Asian region. Each criterion is given a weight that is determined subjectively but by considering the level of importance of each criterion. The weighting of the criteria by using pairwise comparison resulted in: test per population, positive per test, vaccine per population, recovered per positive, deaths per positive. This study produces conclusions that are not much different from the Lowy Institute release. Indonesia is one of the countries where the handling of the Covid-19 pandemic is at a low level, Indonesia is ranked 10th out of 11 countries in the Southeast Asia region, with a utility value 16.29%. Keywords: AHP; COPRAS; covid-19;pairwise comparison; ranking Abstrak: Salah satu lembaga yang menyatakan buruknya penanganan Covid-19 di Indonesia adalah Lowy Institute. Pada 13 Maret 2021 menempatkan Indonesia di peringkat 89 dari 102 negara yang berhasil disurvei berkenaan dengan penanganan pandemi Covid-19. Penelitian ini merupakan upaya kritisi terhadap penilaian Lowy Institute. Digunakan metode hibrid COPRAS-AHP. Metode AHP, khususnya pada bagian pairwise comparison digunakan sebagai metode untuk menentukan validitas bobot kriteria. Digunakan lima kriteria dalam menentukan pemeringkatan penanganan pandemi Covid-19 pada negara-negara di kawasan Asia Tenggara. Masing-masing kriteria diberikan bobot yang ditentukan secara subjektif namun dengan mempertimbangkan tingkat kepentingan masing-masing kriteria. Pembobotan kriteria dengan menggunakan pairwise comparison menghasilkan: kriteria tes per populasi, positif per tes, vaksin per populasim, sembuh per positif, meninggal per positif. Penelitian ini menghasilkan kesimpulan yang tidak jauh berbeda dengan rilis Lowy Institute. Indonesia adalah salah satu negara dengan penanganan pandemi Covid-19 berada dalam level yang relatif rendah, peringkat 10 dari 11 negara di kawasan Asia Tenggara, dengan nilai utilitas 16,29 %. Kata kunci: AHP; COPRAS; covid-19; pairwise comparison; pemeringkatan